1998
DOI: 10.1182/blood.v92.11.4072.423k33_4072_4079
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Residual Disease Status Before Allogeneic Bone Marrow Transplantation Is an Important Determinant of Successful Outcome for Children and Adolescents With Acute Lymphoblastic Leukemia

Abstract: The efficacy of allografting in acute lymphoblastic leukemia (ALL) is heavily influenced by remission status at the time of transplant. Using polymerase chain reaction (PCR)-based minimal residual disease (MRD) analysis, we have investigated retrospectively the impact of submicroscopic leukemia on outcome in 64 patients receiving allogeneic bone marrow transplantation (BMT) for childhood ALL. Remission BM specimens were taken 6 to 81 days (median, 23) before transplant. All patients received similar conditioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 45 publications
4
46
2
Order By: Relevance
“…The quality of remission before BMT may impact upon outcome (Giona et al, 1994;Mehta et al, 1994). Three studies have shown that a low level of disease before transplant correlates with successful outcome (Knechtli et al, 1998a;Uzunel et al, 2001;Van der Velden et al, 2001). This conclusion cannot be drawn from our data.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The quality of remission before BMT may impact upon outcome (Giona et al, 1994;Mehta et al, 1994). Three studies have shown that a low level of disease before transplant correlates with successful outcome (Knechtli et al, 1998a;Uzunel et al, 2001;Van der Velden et al, 2001). This conclusion cannot be drawn from our data.…”
Section: Discussioncontrasting
confidence: 73%
“…In contrast, the other studies were not as restrictive in patient selection. The transplant regimen also did not include T-cell depletion, as performed in two other studies (Knechtli et al, 1998a;Van der Velden et al, 2001). Knechtli et al (1998b) also analysed the post-engraftment behaviour of residual leukaemia after allo-BMT in 71 children with ALL using a semi-quantitative PCR-based method on bone marrow samples taken at four different times post BMT.…”
Section: Discussionmentioning
confidence: 99%
“…For intensive therapy, data are scarcer. Knechtli et al (1998) studied MRD before allogeneic transplantation in 64 children with ALL. The relapse rates for MRD prior to transplantation were 100% for an MRD 10 )2 ) 10 )3 , 64% for an MRD 10 )3 ) 10 )5 and 37% for an MRD < 10 )5 .…”
Section: Methodsmentioning
confidence: 99%
“…Each of these studies has shown MRD burden pre-SCT to be an independent prognostic factor in prediction of relapse. Analysis identified MRD to be an independent prognostic factor in multivariate analysis in Bader et al (2002) and Knechtli et al (1998) (P < 0AE01). Although formal metaanalysis is invalidated by differences in transplant protocol and MRD method, some clinically useful conclusions can be inferred from pooling the results of these studies.…”
Section: Impact Of Mrd Burden Pre-sct On Risk Of Relapsementioning
confidence: 98%
“…Three published studies have examined the correlation between MRD burden prior to conditioning and relapse after SCT in more than 100 children transplanted for ALL in remission (Knechtli et al, 1998;Van der Velden et al, 2001;Bader et al, 2002). Knechtli et al (1998) used polymerase chain reaction (PCR) analysis of antigen receptor genes and allele-specific probing (a technique capable of detection of one leukaemic cell in 10 000 normal cells) to estimate MRD a median of 23 d pre-BMT in 64 children (19 CR1, 39 CR2, two CR3 or beyond) transplanted in a single centre predominantly from unrelated donors. The level of MRD was defined as either high positive [presence of a band on polyacrylamide gel electrophoresis (PAGE)], low (negative by PAGE but positive on radio-labelled probing) or negative.…”
Section: Impact Of Mrd Burden Pre-sct On Risk Of Relapsementioning
confidence: 99%